Prevalence and determinants of self-medication consumption of antibiotics in adults in Iran: a population based cross-sectional study, 2019–2020 - Nazari, Javad; Ghafoury, Roya; Chezani-Sharahi, Nahid; Moradzadeh, Rahmatollah; Naghshbandi, Mobin (Frontiers in Public Health, 2024)
IntroductionThe self-medication of antibiotics is a global crisis, posing a significant challenge to healthcare systems worldwide. This study aimed to investigate the frequency of self-medication in the adult population and the factors influencing it.MethodsThis population-based cross-sectional study was conducted in Arak, a city in central Iran, from January 2019 to January 2020. Stratified random sampling was used to determine the recruitment criteria, and a total of 6,692 individuals participated in the study. Self-medication of antibiotics was defined as the self-reported annual consumption of antibiotics, as well as a record of antibiotic use registered in insurance services during the same period. The variables examined in this study included age, gender, educational level, occupational status, insurance coverage, and marital status. All gathered data were analyzed using SPSS version 16.0 and STATA version 16.0 software. p-values < 0.05 were considered statistically significant.ResultsThe annual prevalence of antibiotic self-medication was 30.3% (n = 2,033). Chi-square and Mann–Whitney tests identified a significant correlation between educational level and self-medication practices (p = 0.028), while no significant associations were observed with gender, occupation, insurance coverage, or marital status. Logistic regression analysis revealed that female participants were less likely to self-medicate (p = 0.027), and both older age and higher levels of education were associated with a reduced likelihood of antibiotic self-medication (p = 0.001 and p = 0.044, respectively).ConclusionFactors such as female gender, older age, and higher education levels are significant determinants affecting antibiotic self-medication.